Entrepreneurship Motivation and Managerial Skills Training for Sugar Palm Farmers in Langke Village, North Gorontalo Regency - Mardin, Herinda; Taan, Hapsawati; Hasan, Fardyansjah; Anas, Muhammad; Sudiarta, I Made; Hasanuddin, Hasanuddin; Dako, Amirudin Y. (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2024)
The Langke village community is known as a community where the majority of its residents work as sugar palm farmers. Palm trees have become the main source of livelihood in this village, because almost every family there depends on their income from processed palm products, such as palm sugar and sap. Motivational training and entrepreneurial managerial skills for sugar palm farmers in Langke village is a strategic step to increase the capacity and economic independence of the local community. This training aims to foster an entrepreneurial spirit in sugar palm farmers so that they not only focus on production, but also have the skills to manage their business professionally. Through the motivation provided, farmers are encouraged to see the potential of the sugar palm business as an opportunity to improve their standard of living and play a role in driving the village economy. This activity was carried out on Saturday 4 October 2024 at the Langke village office hall, Gentuma Raya District, North Gorontalo Regency. The method of this service activity is in the form of training and lectures. Service activities in the form of Motivational Training and Entrepreneurial Managerial Skills for Sugar Palm Farmers in Langke Village, North Gorontalo Regency, have had a positive impact in increasing farmers' understanding and entrepreneurial skills. Through this training, sugar palm farmers are equipped with better managerial skills, which are very useful in managing their farming business and increasing the added value of their products. Apart from that, motivational training helps increase farmers' enthusiasm and self-confidence to continue to develop and innovate, so that it is hoped that they can open wider market access and create better economic opportunities for village communities.